Teaching real-time with a scheduler simulator - Manacero, A. [UNESP]; Miola, M. B. [UNESP]; Nabuco, V. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
In this paper we describe a scheduler simulator for real-time tasks, RTsim, that can be used as a tool to teach real-time scheduling algorithms. It simulates a variety of preprogrammed scheduling policies for single and multi-processor systems and simple algorithm variants introduced by its user. Using RTsim students can conduct experiments that will allow them to understand the effects of each policy given different load conditions and learn which policy is better for different workloads. We show how to use RTsim as a learning tool and the results achieved with its application on the Real-Time Systems course taught at the B.Sc. on Computer Science at Paulista State University - Unesp - at Rio Preto.
Keywords: Hard real-time tasks; Real-time scheduling; Simulators; Algorithms; Computer science; Computer simulation; Curricula; Real time systems; Scheduling; Students; Teaching; Scheduler simulator; Software Package RTsim; Engineering education